Maternal Diet during Exclusive Breastfeeding can Predict Food Preference in Preschoolers: A Cross-Sectional Study of Mother-Child Dyads in Enugu, South-East Nigeria - N. Uwaezuoke, Samuel; I. Eneh, Chizoma; K. Ndu, Ikenna; Iloh, Kenechukwu; I. Udorah, Maria (International Journal of Child Health and Nutrition, 2017)
Background: The relationship between food preference in early childhood and prenatal exposure to flavor in the amniotic fluid is well documented. Although its association with flavor transmission in the breast milk has also been noted, it is poorly reported in this country. Objective: The present study aims to determine the relationship between mothers’ dietary exposure during exclusive breastfeeding and food preference in their preschool-aged children. Methods: Two hundred and twenty (220) mother-child dyads who met the study criteria were enrolled. A pre-tested, structured questionnaire was administered to the mothers. The relationship between maternal consumption of flour-based snacks and staple foods during exclusive breastfeeding and the child’s preference for these foods was determined using risk estimates. After controlling for potential confounders, logistic regression was used for multivariate analysis. Statistical significance was determined at p < 0.05 and all the risk estimates were presented as odds ratios (OR) at 95% confidence intervals (CI). Results: The relationship between daily maternal exposure to staple foods during exclusive breastfeeding and the children’s preference for this variety of food was not statistically significant (p = 0.847, OR= 1.083, 95% CI = 0.481-2.437). However, the children’s preference for flour-based snacks was significantly related to weekly or fourth-nightly maternal exposure to similar diet during exclusive breast feeding (p = 0.035, OR = 2.405, 95% C.I = 1.064 - 5.435). Conclusion: Transmission of flavor in the breast milk may contribute in shaping children’s feeding behavior early in life.